Management of Overseas Acquisitions by Developing Country Multinationals and Its Performance Implications: The Indian Example. (13th April 2016) - Kale, Prashant; Singh, Harbir
Abstract : Developing‐country multinationals (DMNCs) make overseas acquisitions to leverage extant capabilities of acquired companies in order to enter foreign markets and acquire their know‐how to enhance their own competitiveness against global competition at home and abroad. We go "inside the black box" to examine how DMNCs manage those acquisitions and the attendant implications for postacquisition performance. When DMNCs keep the acquired firm "structurally separate" from their own organization and retain its senior executives, they exhibit better acquisition performance. Also, "linking mechanisms" to coordinate interdependencies between the two firms improves performance, especially when the acquired firm is kept structurally separate. Analyses of large‐sample data of Indian DMNCs' overseas acquisitions show that DMNCs' light‐handed approach to managing acquisitions, despite acquiring majority ownership in them, seems suited to their acquisition objectives. © 2016 Wiley Periodicals, Inc.